Improving crop productivity and nitrogen use efficiency using sulfur and zinc-coated urea: A review - Mustafa, Ayesha; Athar, Fareeha; Khan, Imran; Chattha, Muhammad Umer; Nawaz, Muhammad; Shah, Adnan Noor; Mahmood, Athar; Batool, Maria; Aslam, Muhammad Talha; Jaremko, Mariusz; Abdelsalam, Nader R.; Ghareeb, Rehab Y.; et al. (Frontiers in Plant Science, 2022)
Nitrogen (N) is an important macro-nutrient required for crop production and it is considered as an important commodity for agricultural systems. Urea is an important N source which is widely using across the globe to fulfill the crop N requirements. However, N applied in the form of urea is mostly lost which is posing serious economic and environmental issues. Therefore, in this context different approaches like use of coated urea with different substances is using across the globe to reduce the N losses. The urea coating is considered to be an imperative approach to enhance the crop production and reduce the corresponding nitrogen losses and impacts on environment. Under the current scenarios where food security’s bells start ringing now to meet the demand of food for nowadays and upcoming generations, best management strategy is to coat urea with different nutrients such as sulfur (S) and zinc (Zn). The coated urea is slow-release and remains in the soil for prolong period to meet the demand of crop plants which increases nitrogen use efficiency (NUE), growth, yield and grain quality. These nutrient-coated urea reduce nitrogen losses (volatilization, leaching, and N2O) and save the environment from degradation. Sulfur and zinc-coated urea also reduce nutrient deficiencies and have synergetic effects with other various macro and micronutrients on crop. Therefore, to better appraise the potential of sulfur and zinc coated urea: here in this review we discussed the dynamics of S and Zn coated urea in soil, impacts of S and Zn coated urea on crop production, nitrogen use efficiency (NUE), residual and toxic effects of coated urea and constraints of adopting coated fertilizers. Additionally, we also shed light on agronomic and molecular approach to enhance NUE for better crop productivity to meet the food security challenges.